Requirements for the Interaction With Highly Automated Construction Site Delivery Trucks - Colley, Mark; Mytilineos, Stefanos; Walch, Marcel; Gugenheimer, Jan; Rukzio, Enrico (Frontiers in Human Dynamics, 2022)
Automated trucks for long-distance journeys seem within reach. With such automation, no human driver could be available. However, the last mile of the delivery is likely to involve humans. Therefore, either a human driver should still be present, or construction site workers must interact with the automated truck. While automated trucks capable of dealing with various construction sites could be feasible, the development could be costly and time-consuming. To define cooperative solutions for automated deliveries incorporating interaction between automated trucks and humans, a workshop with truck drivers (N = 7) was conducted. Based on this workshop, a model of the delivery process, including communication needs, is proposed. Requirements addressing the issues for highly automated delivery are derived from this process.